Investigation of Distortions in Gamma Camera Scintigraphic Pictures - Siwicki, H.; Gwiazdowska, Barbara A.; Tołwiński, J.; Jasiński, W. K. (Nuklearmedizin - NuclearMedicine, 1971)
The aim of the work was to investigate the magnitude of distortions observed in a scintillation camera display. A Nuclear-Chicago Pho/Camera II combined with 1600-channel analyzer was used for these studies. The measurements were carried out with point, line and volume source of 99mTc. Significant variations of count rates registered, depending on the method of registration of radioactivity were observed across the face of the crystal.